The Position of People as Legal Subjects: Analysis of the Concepts of Maturity and Authority - Teguh Ibadurrahman; Jannatun Naim; Sahman Azhari Mtd; M Fikri Haiqal; Alvito Audryanza Saragih (ISNU Sumatera Utara, 2025)
A person's status as a legal subject depends heavily on their maturity and legal authority. In Indonesia, maturity is defined as 21 years of age according to the Civil Code (KUHPerdata), although there are exceptions for those who marry before that age. Meanwhile, in Islamic law, maturity is more defined by physical and psychological maturity, with the general age limit being 15 years. This maturity directly impacts legal authority, which includes the capacity to enter into contracts, manage property, and be responsible for criminal acts. Minors and legally incompetent individuals require legal protection through a guardian or custodian to prevent potential abuse. The implications of this imbalance in legal authority, both for children and incapacitated individuals, give rise to the need for protection mechanisms, such as pardons or guardianship. This research aims to provide an understanding of the relationship between maturity and legal authority and solutions to this imbalance in the Indonesian legal system. Therefore, legal protection for legally incompetent individuals is essential to achieving justice and preventing exploitation.